Improvement in relapse recovery with peginterferon beta-1a in patients with multiple sclerosis. (November 2016) - Scott, Thomas F; Kieseier, Bernd C; Newsome, Scott D; Arnold, Douglas L; You, Xiaojun; Hung, Serena; Sperling, Bjoern
Background: Subcutaneous peginterferon beta-1a every 2 weeks significantly affects clinical outcomes in patients with relapsing–remitting multiple sclerosis (RRMS). Objectives: To explore relationships between relapses and worsening of disability in patients with RRMS, and assess the treatment effect of peginterferon beta-1a on relapse recovery. Methods: Post-hoc analysis of the 2-year, randomized, double-blind, parallel-group, Phase 3 ADVANCE study. The severity of relapses, proportion of patients with relapses associated with residual disability (onset of 24-week confirmed disability progression (CDP) within 90 days following a relapse), and persistence of changes in Functional Systems Scores, were compared between treatment groups. Results: Subcutaneous peginterferon beta-1a every 2 weeks significantly reduced the proportion of patients experiencing relapse associated with CDP over 2 years (6.6%, compared with 15.1% of patients who received placebo in Year 1; p = 0.02). Reduction in relapses associated with residual disability was greater than the treatment effect on overall relapse rate, and occurred despite similar relapse severity across treatment groups. Conclusions: The beneficial effect of peginterferon beta-1a on risk of CDP may be attributable to the combination of an overall reduction in the risk of relapses and improvement in recovery from relapses, thus limiting further disability progression. Trial registration: ClinicalTrials.gov identifier: NCT00906399